Looking into the eye of patients with chronic obstructive pulmonary disease: an opportunity for better microvascular profiling of these complex patients. Issue 6 (16th May 2018) - Vaes, Anouk W.; Spruit, Martijn A.; Theunis, Jan; Goswami, Nandu; Vanfleteren, Lowie E.; Franssen, Frits M.E.; Wouters, Emiel F.M.; De Boever, Patrick
Abstract: Chronic obstructive pulmonary disease (COPD) is a complex disease with many patients suffering from cardiovascular comorbidity. However, cardiovascular diseases remain often undiagnosed in COPD. Assessment of the retinal microvasculature can provide value in cardiovascular profiling of these patients. Retinal microvascular assessment carried out via a noninvasive eye exam represents an easy to use tool when examining patients with COPD. The purpose of this review was to provide an overview of studies assessing structural and functional changes in the retinal microvasculature of patients with COPD. Findings demonstrated that structural and functional microvascular changes were more common and severe in COPD patients as compared to non‐COPD controls, although few retinal investigations have been performed in patients with COPD. As cardiovascular comorbidities are highly prevalent in COPD, we advocate more research to investigate the value of an eye exam for microvascular phenotyping of COPD patients.